Characterization of Fed Cattle Mobility during the COVID-19 Pandemic - Sage Mijares; Michelle Calvo-Lorenzo; Nick Betts; Lacey Alexander; Lily N. Edwards-Callaway (Animals, 2021)
The COVID-19 pandemic had significant consequences on cattle slaughter capacity in the United States. Although industry stakeholders implemented strategies to minimize cattle welfare impacts of increased weights, days on feed (DOF), and increasing temperatures, there were concerns that mobility challenges would be observed at slaughter facilities. The objectives of this study were to characterize mobility in fed cattle during this recovery period and to identify factors impacting mobility. A total of 158 groups of cattle (15,388 animals) from one slaughter facility were included in the study. A 4-point mobility scoring system was used to assess cattle mobility. Cattle at the facility with normal mobility scores were reduced from the historical average of 96.19% to 74.55%. No increase in highly elevated mobility scores was observed. Mobility was impacted by weight, temperature humidity index (THI), distance hauled, sex, and DOF, with results differing by mobility category. Weather was a key contributor to mobility challenges; the relative risk of observing an elevated mobility score was 45.76% greater when the THI changed from No Stress to Mild Stress. Despite the challenges that the industry faced during this period, efforts to minimize negative effects on cattle welfare by enhanced focus on low-stress handling were effective.